2017
DOI: 10.1111/cpr.12405
|View full text |Cite
|
Sign up to set email alerts
|

Emerging roles of MicroRNAs in osteonecrosis of the femoral head

Abstract: Osteonecrosis of the femoral head (ONFH) is one of the most common orthopaedic diseases. The exact pathogenic mechanism of ONFH is still unknown. MicroRNAs

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
42
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(42 citation statements)
references
References 49 publications
0
42
0
Order By: Relevance
“…EVs that are released by cells such as BMSCs and osteoblasts can deliver miRs that are engaged in the development of ONFH. 28,29 For instance, miR-122-5p overexpressed in BMSC-derived EVs suppresses the expression of RTK signalling antagonist 2 to inhibit the occurrence of ONFH through RTK/ Ras/mitogen-activated protein kinase axis. 30 Moreover, miR-26a-CD34-EVs strengthened the osteogenic differentiation of BMSCs and the integrity of trabecular bone in glucocorticoids-induced ONFH.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…EVs that are released by cells such as BMSCs and osteoblasts can deliver miRs that are engaged in the development of ONFH. 28,29 For instance, miR-122-5p overexpressed in BMSC-derived EVs suppresses the expression of RTK signalling antagonist 2 to inhibit the occurrence of ONFH through RTK/ Ras/mitogen-activated protein kinase axis. 30 Moreover, miR-26a-CD34-EVs strengthened the osteogenic differentiation of BMSCs and the integrity of trabecular bone in glucocorticoids-induced ONFH.…”
Section: Discussionmentioning
confidence: 99%
“…Subsequently, we identified that the expression of miR‐148a‐3p was poorly expressed in ONFH, and miR‐148a‐3p in EVs derived from BMSCs promoted the proliferation and osteogenic differentiation of BMSCs in ONFH. EVs that are released by cells such as BMSCs and osteoblasts can deliver miRs that are engaged in the development of ONFH 28,29 . For instance, miR‐122‐5p overexpressed in BMSC‐derived EVs suppresses the expression of RTK signalling antagonist 2 to inhibit the occurrence of ONFH through RTK/Ras/mitogen‐activated protein kinase axis 30 .…”
Section: Discussionmentioning
confidence: 99%
“…Recently, the potential for using miRNA to treat ONFH has attracted increasing attention 35 . Yamasaki et al 36 .…”
Section: Discussionmentioning
confidence: 99%
“…Deregulation of miRNAs contributes to ONFH-N [ 22 ], but the differentially expressed circulating miRNAs in patients with ONFH-N receiving conservative therapy are unknown. Therefore, this study aimed to determine the differentially expressed miRNAs in patients with ONFH-N receiving conservative treatments.…”
Section: Discussionmentioning
confidence: 99%